MECHANISM OF ADAPTIVE QUALITY MANAGEMENT OF TRAINING APPLICANTS FOR HIGHER EDUCATION WITH THE DEGREE OF DOCTOR OF PHILOSOPHY FOR THE NEEDS OF THE ARMED FORCES OF UKRAINE - Kozubtsov , I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The Armed Forces of Ukraine are interested in highly professional subjects of scientific and scientific-technical activities, namely in highly qualified scientific and scientific-pedagogical workers, whose training is carried out through an adjunct course for obtaining the scientific degree of Doctor of philosophy. The problem of ensuring the quality of higher education for applicants for the degree of Doctor of philosophy for the needs of the Armed Forces of Ukraine is not solved at present and is relevant. The aim of the study is to substantiate the mechanism of Adaptive Quality Management of training applicants for higher education with a doctor of Philosophy degree for the needs of the Armed Forces of Ukraine. The article analyzes the key experience of recent publications, which showed the interest of a wide scientific circle in the problems of applying adaptive management in the field of education and science. Along with this, researchers have different opinions about the vision of what adaptive management should be. As a result, there is no mechanism of adaptive management in the field of education and science, and even more so in the system of training applicants for higher education with the degree of Doctor of philosophy through adjunct and postgraduate studies. Based on the analysis, it is proposed to choose the basic mechanism of Adaptive Quality Management of training of applicants for higher education of the degree of Doctor of philosophy, which is implemented by a complex methodology for building an individual adaptive learning trajectory and developing the methodological culture of applicants for higher education of the degree of Doctor of philosophy, which includes a set of design methods: 1) a variable component of educational and scientific characteristics of applicants for a Scientific School; 2) a variable component of an optional educational and scientific program of a Scientific School; 3) monitoring and diagnostics of the methodological culture of applicants in the context of the general certification procedure. The listed methods of complex methodology are implemented in a scientific school, provided that the supervisor applies an improved model of scientific and methodological support for applicants for higher education with the degree of Doctor of philosophy. Thus, a scientific novelty is obtained, which consists in the fact that for the first time a mechanism for managing the quality of training applicants for higher education for the degree of Doctor of philosophy is proposed on the basis of adaptive management according to the PDCA scheme. The practical significance of the obtained scientific result made it possible to find out the mechanism of Adaptive Quality Management of methodological training of adjuncts and postgraduates. The presented study does not exhaust all aspects of this problem. The theoretical and practical results obtained in the course of scientific research form the basis for its further study in various aspects.